Futures Leads the Spot but Why not so When Market in Shocks? A Time-Varying Price Discovery of Indian Precious Metals - Chanchal Saini; Ishwar Sharma (Colombo Business Journal)
The study empirically measures the average and time-varying contribution of the spot and futures market to the price discovery of benchmark Indian precious metals from June 2005 to March 2023. The two most popular precious metals in India, i.e., Gold and Silver, were selected for the study. The average contribution is measured through VECM (Vector Error Correction Model) and CFW (common factor weights). Additionally, for getting time-varying contribution, VECM is reformulated into state space form and Kalman filter and smoothening are applied for computing time-varying CFW. Findings reveal that price discovery depicts time-varying behaviour during the study period. While most of the time, futures lead the spot, in case of any shocking news, the spot market dominates the futures as noise trading happens in the futures market for both precious metals, i.e., Gold and Silver. Furthermore, futures market volume, volatility, and COVID-19 negatively affect the price discovery in both precious metals.